Problem of optimization of statically indeterminate structures for moving loads - Son, Do (Vietnam Journal of Mechanics, 1980)
In this paper formulated a problem of optimization of statically indeterminate structures for moving loads in the shake-down state by a linear programming using the simplex method. The algorithm and numerical results have been illustrated by the computation of a statically indeterminate beam.